Detection of Spectral Reflective Changes for Temporal Resolution of Land Cover (LC) for Two Different Seasons in central Iraq - Salman, Athraa Ali; Al Ramahi, Fouad K. Mashee (Iraqi Journal of Science, 2022)
The purpose of the study is the city of Baghdad, the capital of Iraq, was chosen to study the spectral reflection of the land cover and to determine the changes taking place in the areas of the main features of the city using the temporal resolution of multispectral bands of the satellite Landsat 5 and 8 for MSS and OLI sensors respectively belonging to NASA and for the period 1999-2021, and calculating the increase and decrease in the basic features of Baghdad .The main conclusions of the study were, This study from 1999 to 2021 and in two different seasons: the Spring of the growing season and Summer the dry season. When using the supervised classification method to determine the differences, the results showed remarkable changes. Where he was in 1999 Normalized Difference Vegetation Index (NDVI) 925km2 and Normalized Difference Water Index (NDWI) 75.3km2 In the case of an increase during the growth period, while the values decreased during the period of dry to (NDVI) 390.8km2 and (NDWI) 51.9km2.As for Soil Adjusted Vegetation Index (SAVI) 1692.9km2 and Normalized Difference Built up Index (NDBI) 782.1km2 we notice a decrease in the growth period, while the values increase during the dry period to (SAVI) 2239.1km2 and (NDBI) 1495.7km2. In 2021 (NDVI) 242.7km2 (NDWI) 83.4km2 in the case of an increase during the growth period, while the values decreased during the period of dry to (NDVI) 122.2km2 and (NDWI) 73.2km2 .As for (SAVI) 3016.3km2 (NDBI) 1263.3km2 we notice a decrease in the growth period, while the values increase during the dry period to (SAVI) 3702.3km2 and (NDBI) 1882.2km2. Where most of the changes in LC were due to human activities, and the most prominent changes in LC were due to urban expansion on agricultural lands continuously in all years that resulted from land degradation.